RANCANG BANGUN SISTEM INFORMASI AKADEMIK SEKOLAHBERBASIS WEBSITE DI SMP NEGERI 1 WARUNGKIARA - Rahmat Gunawan (2023)
SMP Negeri 1 Warungkiara school located in Warungkiara District, Sukabumi Regency, West Java. SMP Negeri 1 Warungkiara has not utilized information technology properly so that in providing information to students it is less effective, as well as in disseminating information to students they still use WhatsApp through printed letters and direct announcements. Assessment of learning outcomes also still uses printed manual assessments and in giving grades which is not effective and efficient. In addition, the data becomes duplicated and it is difficult to find which data is the most recent. Therefore, the solution provided is in the form of a website-based school academic information system design. In designing the system build, a development method is needed using the SCRUM research method which can make it easier to design the system and to research this problem using the PIECES method. The results of this study are in the form of a website-based school academic information system that can process data and reports, optimize the performance of school staff, make system procedures more efficient, and make it easier to find information for students.